Photocurrent Density Enhancement of DSSC with Existence of ZnO in TiO2 Based Photoanode - Lusi Safriani; Nurfitriani Nurfitriani; Ayunita Chintia Celline; Annisa Aprilia; Yukio Furukawa (Department of Physics, Sebelas Maret University, 2023)
One of the important components of a dye-sensitized solar cell (DSSC) is photoanode which plays a critical role serving as the center of conversion energy. Photoanode consists of transparent conducting substrate, a semiconductor layer, and dyes molecules as sensitizers. Titanium dioxide (TiO2) is widely used as a photoanode because it is a mesoporous and stable material despite its high recombination rate. To reduce the recombination rate and improve electron transport, TiO2 is combined with other materials such as ZnO to form TiO2/ZnO composites. ZnO is a good choice because it has higher electron mobility than TiO2 to inhibit recombination. The synthesis process of TiO2/ZnO composites was carried out using the sol-gel method with variations in the weight percentage of ZnO. The TiO2/ZnO composite was then applied as a photoanode in DSSC. The J-V measurement results shows that the DSSC with TiO2/ZnO 25wt% composite layer as the photoanode produced the highest efficiency of 0.86%. This increase in efficiency was due to an increase in the photo-current of photoanodes that have more ZnO content. The presence of ZnO leads to faster-moving electron transport, therefore reducing recombination and increasing efficiency.